2015
DOI: 10.1007/s11999-014-3964-4
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Cost Utility Analyses in Total Joint Arthroplasty: A Systematic Review

Abstract: Background Total joint arthroplasty (TJA), although considered to be highly beneficial, is associated with substantial costs to the US healthcare system. Cost utility analysis has become an increasingly important means to objectively evaluate the value of a healthcare intervention from the perspective of both extending the quantity and improving the quality of life. Relatively little is known about the overall cost utility analysis evidence base in TJA. Questions/purposes The goals of this review were to (1) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 39 publications
0
55
0
4
Order By: Relevance
“…For cost-effectiveness analysis, physical or ''natural'' units, such as cases treated or years of life gained, are used; for cost-utility analysis, health state utility values such as QALYs are used; for cost-minimization analysis, only input costs are considered to identify the least expensive way to achieve the same outcome; and for cost-benefit analysis, outcomes are measured in monetary units. The distinction between these analyses is described more fully elsewhere [1,3,4,13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cost-effectiveness analysis, physical or ''natural'' units, such as cases treated or years of life gained, are used; for cost-utility analysis, health state utility values such as QALYs are used; for cost-minimization analysis, only input costs are considered to identify the least expensive way to achieve the same outcome; and for cost-benefit analysis, outcomes are measured in monetary units. The distinction between these analyses is described more fully elsewhere [1,3,4,13].…”
Section: Methodsmentioning
confidence: 99%
“…In this era of increasing cost-consciousness, when cost containment is more important than ever, healthcare economic analyses have become more common in the medical [11] and orthopaedic surgery literature [4]. Some reviews have concluded that many operative interventions in orthopaedic surgery are cost effective [7,13], while another questioned the costeffectiveness of certain procedures [19].…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness, cost-utility, and cost-benefit analyses After appropriate cost identification, cost-effectiveness, costutility, and cost-benefit analyses provide a means to compare the cost of medical interventions with the health benefits gained [26]. Cost-effectiveness analyses use objective outcomes to compare two different interventions (e.g., union rate of both-bone forearm fractures in operatively and nonoperatively treated fractures).…”
Section: Cost Identification Using Time-driven Activity-based Costingmentioning
confidence: 99%
“…A recent systematic review of cost utility analyses in total joint arthroplasty identified 23 U.S. analyses. In 16 of these analyses (70%), $50,000 per QALY threshold was used, two studies used $100,000, one study used both $50,000 and $100,000 and one study used $150,000; three studies did not define a cost effectiveness threshold [11].…”
Section: Updating the Threshold In Orthopedic Surgerymentioning
confidence: 99%